2011
DOI: 10.1007/s10585-011-9388-6
|View full text |Cite
|
Sign up to set email alerts
|

Mena invasive (MenaINV) and Mena11a isoforms play distinct roles in breast cancer cell cohesion and association with TMEM

Abstract: Mena, an actin regulatory protein, functions at the convergence of motility pathways that drive breast cancer cell invasion and migration in vivo. The tumor microenvironment spontaneously induces both increased expression of the MenaINV and decreased expression of Mena11a isoforms in invasive and migratory tumor cells. Tumor cells with this Mena expression pattern participate with macrophages in migration and intravasation in mouse mammary tumors in vivo. Consistent with these findings, anatomical sites contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
119
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(134 citation statements)
references
References 32 publications
14
119
0
1
Order By: Relevance
“…In a xenograft rodent mammary cancer model, the invasive cancer cells showed a decrease of Mena 11a and an increase of Mena INV isoform expression (11), reminiscent of our data. The MENA INV isoform, which has an exon next to the Ena/VASP homology 1 (EVH1) domain, facilitates cell invasion by stabilizing invadopodia (12) and promoting discohesive tumor morphology, whereas MENA 11a expression appears to promote epithelial tumor morphology (30). hMENA 11a , unlike hMENA, is phosphorylated following activation of the EGFR or its other family members, suggesting that exon 11a may represent a site for regulation of hMENA 11a in breast cancer (9).…”
Section: Discussionmentioning
confidence: 99%
“…In a xenograft rodent mammary cancer model, the invasive cancer cells showed a decrease of Mena 11a and an increase of Mena INV isoform expression (11), reminiscent of our data. The MENA INV isoform, which has an exon next to the Ena/VASP homology 1 (EVH1) domain, facilitates cell invasion by stabilizing invadopodia (12) and promoting discohesive tumor morphology, whereas MENA 11a expression appears to promote epithelial tumor morphology (30). hMENA 11a , unlike hMENA, is phosphorylated following activation of the EGFR or its other family members, suggesting that exon 11a may represent a site for regulation of hMENA 11a in breast cancer (9).…”
Section: Discussionmentioning
confidence: 99%
“…These AUC values, where 0.8 is good, 0.7 is fair and 0.6 is poor discrimination (Metz, 1978), indicate that TMEM composite is better at predicting metastasis than these other prognostics (Harney et al, 2015;Oktay and Jones, 2015;Pignatelli et al, 2014;Robinson et al, 2009;Rohan et al, 2014;Roussos et al, 2011c;Wyckoff et al, 2007). Previous reports on cancer angiogenesis and vasculogenesis have collectively demonstrated that newly constructed endothelia are composed of myeloid precursors expressing the receptor tyrosine kinase Tie2 (also known as TEK) (Riabov et al, 2014;Squadrito and De Palma, 2011), and, more recently, the mannose-receptor c-type 1 (MRC1) (Hughes et al, 2015a).…”
Section: Molecular Profiling Of Metastatic Breast Cancer Cell Subpopumentioning
confidence: 93%
“…Recently a splice variant of Mena, termed MenaINV, was found to be overexpressed in breast and colorectal cancers (Di Modugno et al, 2004). Mena deficiency decreases invasion, metastasis and tumour progression in polyoma middle-T transgenic mouse models and impairs normal breast development (Roussos et al, 2011a;Roussos et al, 2010;Roussos et al, 2011c).…”
Section: Filopodiummentioning
confidence: 99%